A rare cause of retinal artery embolism: Accessory mitral valve tissue. Issue 2 (11th January 2018) - Kahyaoglu, Muzaffer; Kalayci, Arzu; Gecmen, Cetin; Sari, Munevver; Guner, Ahmet; Celik, Mehmet; İzgi, Ibrahim Akin and Kirma, Cevat
Abstract : A 42‐year‐old female patient was referred our clinic for investigation of a history of acute retinal artery occlusion. Transthoracic echocardiography showed a cyst‐like, mobile formation on posterior mitral valve leaflet. 2D and real time 3D transesophageal echocardiography showed a flexible circular mobile structure which was attached to posterior mitral valve leaflet. Echocardiographic appearance and morphological characteristics were suggestive of accessory mitral valve tissue.